2020
DOI: 10.1038/s41598-020-71368-1
|View full text |Cite
|
Sign up to set email alerts
|

Reduced monoaminergic nuclei MRI signal detectable in pre-symptomatic older adults with future memory decline

Abstract: Evidence from murine models and human post-mortem studies indicates that monoaminergic nuclei undergo degeneration at the pre-symptomatic stage of Alzheimer’s disease (AD). Analysing 129 datasets from the Alzheimer’s Disease Neuroimaging Initiative (ADNI) and relying on the Clinical Dementia Rating as group-defining instrument, we hypothesised that the MRI signal of monoaminergic nuclei would be a statistically significant predictor of memory decline in participants initially recruited in ADNI as healthy adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Structural and functional alterations of VTA's neurons have been described also in humans. VTA size and its connectivity with the hippocampus was associated with measures of episodic memory in patients with AD and a-MCI [36] and in the pre-symptomatic older adults [37]. As detailed below, specific changes in functional connectivity were also reported between VTA and some critical nodes of the default mode network in patient with AD and a-MCI [38].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Structural and functional alterations of VTA's neurons have been described also in humans. VTA size and its connectivity with the hippocampus was associated with measures of episodic memory in patients with AD and a-MCI [36] and in the pre-symptomatic older adults [37]. As detailed below, specific changes in functional connectivity were also reported between VTA and some critical nodes of the default mode network in patient with AD and a-MCI [38].…”
Section: Introductionmentioning
confidence: 85%
“…In a transgenic model of AD, Nobili et al [30] demonstrated a progressive degeneration of neurons from the ventral tegmental area (VTA) (i.e., a dopaminergic-rich structure located in the midbrain) [31], which correlated behaviourally with reward and memory functions [30,32]. Notably, the mesocortico-limbic system, which is strictly involved in reward [33,35], as well as in executive and memory functions [30,36,37] stems from dopamine neurons located in the VTA midbrain region.…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer’s disease is a complicated and multifactorial disorder, and many hypotheses have been developed, including Aβ ( Selkoe and Hardy, 2016 ), tau ( Arnsten et al, 2021 ), cholinergic ( Terry and Buccafusco, 2003 ; Chen and Mobley, 2019 ), and dopaminergic degeneration ( Nobili et al, 2017 ; Cordella et al, 2018 ; De Marco and Venneri, 2018 ; Serra et al, 2018 , 2021 ; Bozzali et al, 2019 ; Iaccarino et al, 2020 ; Venneri and De Marco, 2020 ; La Barbera et al, 2021 ; Sala et al, 2021 ; Spoleti et al, 2022 ), oxidative stress ( Markesbery, 1997 ), inflammation ( Kinney et al, 2018 ), etc. How much further we have to go before deciphering all the molecular mechanisms underlying the onset and evolution of AD and, in turn, the putative druggable targets of the disease is not yet known, however, many studies have been done to find a potential therapeutic strategy.…”
Section: Alzheimer’s Diseasementioning
confidence: 99%
“…Indeed, stronger loss of gray matter in dopaminergic pathways was also paralleled by a worsening not only of episodic memory but also of behavioral alterations, related to the emergence of psychiatric symptoms and delusions in patients with AD ( 137 ). Given the link between the mesocorticolimbic dopamine and NPS, and the fact that these symptoms speed up the disease progression, it is not surprising that functional disconnection of the VTA with mesocorticolimbic targets can accelerate the conversion from the MCI stage to clinical AD ( 137 , 141 , 142 ).…”
Section: Dopamine In Alzheimer's Diseasementioning
confidence: 99%